DECISION ANALYSIS TO FIND BEST SOLUTION TO OVERCOME INSTRUMENTATION PROBLEMS BY USING ANALYTIC HIERARCHY PROCESS AND SMART METHOD - Ojak Somonggal, Hatian
The Laksmana offshore area is one of the oil field area under Sumatera field. The production from the Laksmana offshore area is 750 BOPD (Barrel Oil per Day). The instrumentation system in Laksmana Offshore area plays a vital role in the production process since instrument equipment controls the Fluid Flow, level, and pressure. Based on the data collected from January 7th, 2020, to December 6th, 2020, there were 13 unplanned shutdowns caused by instrumentation system failures. This instrumentation failure can be grouped into 3 major categories: Air supply compressor Failure, Instrumentation Valve Problems, and Instrument equipment malfunctions. By stratifying the problem using a Pareto diagram, it was found that the problem of air compressor failure is the most significant cause that has the biggest impact. To find the rootcause and the most dominant factor of the problem, the researcher carried out Fishbone diagrams and Failure Mode Effect Analysis (FMEA) combined with Pareto diagrams. The result is that the Company does not yet have methods and facilities to monitor the condition of the compressor in real time, so it is difficult to analyze and know the early signs of air compressor failure. By using the value-focused thinking method, the researcher and the team in the focus group discussion develop alternatives that can be implemented to achieve the fundamental objectives that have been set. There are 4 alternative solutions can be used to solve this problem. The first alternative is installing the HMI(Human Machine Interface/SCADA) system. The second alternative is purchase and use the S551 Data Logger. The third alternative is the assembly of own innovation tools made by the Laksmana's worker, and the last is to appoint extra personnel for daily monitoring of the compressor. This research will use the Analytical Hierarchy Process (AHP) and Simple Multi Attribute Rating Technique (SMART) methods to determine the best solution. Based on the results of the interviews obtained 3 criteria in the value tree. The criteria are in the form of Cost, Benefit, and Risk. The Cost criteria has 1 sub-criteria, namely the installation cost, the benefit criterion has 2 sub-criteria consisting of installation time & accessibility. And the last criterion is risk. It has 2 sub-criteria: the risk of work installation and the risk of human error.The calculations using the AHP and SMART methods obtained the same results. The own innovation tool become the best solution.